Development of quality index method for eviscerated and non-eviscerated octopus (Octopus insularis) - Aragão, Márcia; Garruti, Deborah; Ogawa, Norma; Bezerra, Viviane; Silva, Elisabeth Mary (Revista Ciência Agronômica, 2019)
This work aimed to develop a Quality Index Method (QIM) for octopus species Octopus insularis and apply it to samples of eviscerated and non-eviscerated specimens in order to establish stability in cold storage. Initially we carried out the recruitment of judges, who were trained to verify the changes undergone by the octopus during storage under refrigeration. The development of QIM Table took place in three experiments. At first, a QIM Table for Octopus vulgaris from literature was presented to judges together with specimens of O. insularis, so they could assess whether the parameters were suited to this specie.  In the second experiment the objective was to validate the table, verifying if changes were needed in the predefined parameters or if it was also necessary to add new ones. Finally, the QIM Table was applied to determine the shelf life of non-eviscerated (NEV) and eviscerated (EV) octopuses (O. insularis) during refrigerated storage (2 ± 2 °C). The sum of demerit points for all parameters was named Quality Index (QI). To determine the value of QI at rejection point, N-TVB and N-TMA contents were determined. The data were submitted to analysis of variance and Tukey test at 5% significance, besides correlation and regression analysis by the GLM routine. The developed Quality Index Method for Octopus insularis consists of 8 parameters, totalizing 24 demerit points. The NEV samples were rejected at the tenth day of storage, while the rejection of EV samples occurred only at the end of the experiment.